THE RELEVANCE OF THE BRAZILIAN AMAZON FOR THE RELATIONSHIP BETWEEN BRAZIL AND THE EUROPEAN UNION - Døhlie Saltnes, Johanne; Granja e Barros, Ana Flávia; Søndergaard, Niels (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2024)
There is plentiful scientific literature about the importance of the Amazon Forest to climate regulation and biological diversity drawing from analytical frameworks such as the Anthropocene, “planetary boundaries” and “Earth System Governance”. In the Brazilian case, the forest is part of the Legal Amazon region, which comprises other biomes also threatened by the recent and predatory expansion of the agricultural frontiers, as well as other illegal activities. They violate the rights of more than thirty-eight million local inhabitants, especially indigenous communities (Fellows et al, 2023). In this context, we raise the question: how is the Legal Amazon important for the relationship between Brasilia and Brussels? We contend Brazilians keep the national approach on the Legal Amazon, while the Europeans have a more global view, but focusing on the forest. From an international political economy perspective, the two tipping points chosen were the signature of the trade agreement between the European Union (EU) and Brazil in 2019, and the European Regulation on Deforestation-free products of 2022. In this context of valorization of the standing forest and the ecosystem services it provides, this article aims to analyse the relevance of the Legal Amazon to the relationship between the EU and Brazil, based on the concept of “deforestation-free value chains”, which is the basis of the most recent European regulations within the Green Deal. The method consists of the analysis of official documents and data from the EU and Brazil, as well as recent scientific literature in international law and international relations. Our main premise is that the EU has been playing the role of exporter of rules (norm-maker) to promote the bloc’s trade and environmental interests. Also, the EU acts to influence decision-making processes within multilateral negotiations (norm-shaper). Concerning the forest, two telling examples are the climate change and biodiversity regimes. However, the promotion of European interests engenders profound divergences from Brazilian interests. Therefore, the political stands of both sides explain the very long negotiations that led to the 2019 trade agreement. Likewise, divergences have marked the unfolding of the climate change regime after the Paris Agreement, and the Post-2020 Biodiversity Framework, adopted in 2022. In the same vein, the 2022 deforestation ban will bring new challenges to the relationship between Brazil and the EU. The main findings are that the forest is of the utmost importance because there is a clear connection between the European acknowledgment of its role as a consumer of commodities that sustain deforestation around the world and the Brazilian failure to effectively fight deforestation, notably in the last four years, under President Bolsonaro. Finally, we conclude that Brussels has taken extremely ambitious but necessary steps to fight deforestation trends. In this sense, the relationship between Brazil and the EU is strongly marked by the trade-environmental agenda, having the Amazon Forest at its core. The EU has been imposing new patterns of traceability and sustainability on third countries. While the EU plays the role of norm-maker and exporter, Brazil is challenged by the condition of ending deforestation to maintain access to the European market. Although both actors have some colliding views and preferences, there are opportunities to build a better strategic partnership, based on global sustainability priorities now. Keywords: Deforestation-free value chains. Legal Amazon. EU. Brazil.